Didactical Analysis of Mathematical Literacy Skills to Identify Learning Obstacles on Space and Shape Content - Kardila; Suharti; Husna, Asmaul; Mardiana; Ulpa, Maria (Department of Mathematics Education, 2023)
Mathematical literacy can be defined as the ability to understand and use mathematics in various contexts to solve problems, geometry is a lesson that can still make students experience learning obstacles or called learning obstacles. The purpose of the study was to identify learning obstacles and didactically analyze students' mathematical literacy on space and shape content. This research uses a qualitative method, incorporating the dedactical design model (Didactical Design Research). The qualitative method consists of interviews, observations, and documentation studies. The instruments used were interview guidelines and observation guidelines. Meanwhile, the dedactical design consists of: 1) prospective analysis (before learning) 2) metapedactic analysis and 3) retrospective analysis (combined results of prospective and metapedactic analysis). The research subjects were 6 students who were selected by purposive sampling. Based on the dedactical design, the researcher only reached the prospective stage. Based on the results of research on students' mathematical literacy skills in solving PISA questions on space and shape content, namely on the three subjects showing different results. Based on the written test results, AD and AL subjects have high mathematical literacy skills. then JU subjects have moderate literacy skills. And subjects NF, RI and MA have low mathematical literacy skills. So that from these three subjects it can be said that the students' mathematical literacy skills are still low. Efforts that can be made based on learning obstacles are that students are guided and familiarized when given problems to solve by starting to write what is known and what is asked in the given problem, linking to real-world concepts, expressing arguments in solving problems, developing strategies, using symbols, mathematical tools, and making conclusions of mathematical solutions.